Effects of child's autism on the father - Del Rosario, Maria Theresa G. (2008)
It was the aim of this study to find out the personal experiences of fathers in raising their child with autism, the effects of the disability to them and their coping strategies considering the demands expected from them. Twenty fathers from ages 31-55 years old took part in this study. A survey questionnaire, 33-item Sentence Completion Form (SCF) and interviews were used to elicit information. As a result of the presence of a child with autism in the family, young and old fathers experienced parental stress in raising their special child. Primarily, fathers coped anchoring on their faith in God but younger fathers coped also by intellectually enriching themselves about autism. The creation of a support group for fathers only was highly recommended along with the inclusion of family systems theory in SPED courses and organization of forums about family dynamics.